A new record of the Late Cretaceous cirripede Eoverruca hewitti (Verrucomorpha, Proverrucidae) from southern Poland - Jagt, John W. M.; Jaskuła, Iwona; Witek, Anna; Jagt-Yazykova, Elena A. (Zootaxa, 2008)
Isolated valves of proverrucid cirripedes (Thoracica, Verrucomorpha) from upper lower Campanian strata exposed at Jeżówka, near Wolbrom (southern Poland), are shown to be conspecific with the type (and sole) species of the genus Eoverruca, E. hewitti Withers, 1935. This species was first recorded from the upper Santonian (Marsupites testudinarius Zone, Uintacrinus Band in Withers’s terminology) at East Harling, Norfolk and at Wattisfield, Suffolk (eastern England). To our knowledge, there have been no subsequent records of this taxon. In general, proverrucids are rare fossils, with but a handful of species known to date from the upper Turonian to upper Maastrichtian (and possibly lower Paleocene) of northwest Europe (Rügen, Germany; eastern England; the Liège-Limburg Basin in northeast Belgium and southeast Netherlands; present record from southern Poland). In part, this undoubtedly reflects collection failure; because of diminutive size, valves of E. hewitti have probably been frequently overlooked. In addition, the species may have had special ecological requirements, and thus be restricted to particular facies types. The present material originates almost exclusively from glauconite-rich levels just below a hardground, with none or very few other cirripede species associated.